Preparation method of a copper-nickel based catalyst and its application in ethanol conversion to acetonitrile
By preparing copper-nickel-based catalysts, the problems of short life and high energy consumption of ethanol dehydrogenation catalysts are solved, and high efficiency and low energy consumption are achieved. It has the advantages of simple operation, low cost and good stability.
Patent Information
- Application Number
- CN202111457590.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-01
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-12-01
AI Technical Summary
The existing ethanol dehydrogenation catalysts have problems such as short catalytic life and high ammonia alcohol ratio leading to large energy consumption, which limits their industrial applications.
A copper and nickel-based catalyst is prepared by mixing copper salt with ammonia water, calcining, mixing it with nickel salt again and reducing treatment, and a catalyst supported by copper and nickel is prepared for ethanol dehydrogenation reaction. The process includes the reaction and calcination steps under specific temperature and pH conditions, and the introduction of nickel by ammonia distillation or impregnation method to form a copper-nickel-based catalyst with high activity and stability.
The yield of acetonitrile and the stability of the catalyst are significantly improved, the by-product generation during the reaction process is reduced, the service life of the catalyst is improved, and the production of acetonitrile with low energy consumption and high efficiency is achieved.
Smart Images

Figure BDA0003387075520000081 
Figure BDA0003387075520000091 
Figure HDA0003387075530000011
Abstract
Description
Technical Field
[0001] The present application belongs to the field of bioenergy chemical technology, and specifically relates to a method for preparing a copper-nickel based catalyst and its application in the conversion of ethanol to acetonitrile. Background Art
[0002] Acetonitrile is an important bulk chemical. It is not only an extraction solvent for separating butadiene and isoprene in the petrochemical industry, but is also widely used in pesticides, medicines, semiconductors and other fields, and the market demand is increasing year by year. Acetonitrile is mainly derived from the by-product of the process of producing acrylonitrile by ammoxidation of propylene. It needs to be separated and purified in multiple steps, and its output is limited by the acrylonitrile production capacity. In addition, the process of producing acetonitrile by ammoniation of acetic acid has problems such as strong corrosiveness of raw materials, rapid deactivation of catalysts, and difficulty in continuous production.
[0003] In comparison, the ethanol dehydrogenation amination method for producing acetonitrile has the characteristics of wide raw material sources, good atom economy, high selectivity, and can co-produce hydrogen, making it a potential green synthesis process.
[0004] In the study of ethanol dehydrogenation and amination to acetonitrile, the selection of catalyst active components and carriers and the preparation method have a substantial impact on the reaction activity and stability of the catalyst. The dehydrogenation active centers are concentrated on non-precious metals such as Cu, Ni, and Co. Card et al. first reported the use of Cu / Al2O3 and CuZn / Al2O3 catalysts in the early 1980s, and obtained an acetonitrile single-pass yield of 87% at a reaction temperature of 325°C (J.Org.Chem., 1981, 46, 754-757.). Subsequent studies focused on the use of oxides with acidic sites such as γ-Al2O3 and ZrO2 as carriers. For example, Northeast Petroleum University reported the use of copper as an active component loaded on Al2O3, ZrO2, NiO and ZnO carriers to obtain an acetonitrile yield of more than 80% within 10 hours (CN103949252A; Chemical Industry Progress, 2011, 30, 1013-1018.). Hebei University of Technology reported the use of Co 19.9 Ni 3.0 / γ-Al2O3 catalyst catalyzes the dehydrogenation and amination of ethanol, which can obtain an initial acetonitrile selectivity of 92%, but the acetonitrile selectivity gradually decreases as the reaction proceeds (Cata. Commun., 2009, 10, 1454–1458). Tsinghua University reported the use of a metal oxide catalyst composed of Cu, Zn, Al, Ti, La or Ce for the dehydrogenation and amination of ethanol, obtaining a mass yield of 66% acetonitrile. Xi'an Yuanchuang Chemical Technology Co., Ltd. reported a catalyst preparation method in which chelated copper and nickel are dispersed in alumina microspheres, which can obtain an acetonitrile selectivity of more than 90% (CN108187680A). At present, the catalyst for the dehydrogenation and amination of ethanol still has problems such as short catalytic life and high energy consumption due to high ammonia-alcohol ratio, which limits its industrial application. Summary of the invention
[0005] The purpose of the present application is to provide a preparation and application of a copper-nickel based catalyst. The method has the advantages of simple operation, low catalyst cost, economy and practicality, high efficiency in producing acetonitrile, and low energy consumption.
[0006] According to one aspect of the present application, a method for preparing a copper-nickel based catalyst is provided, comprising at least the following steps:
[0007] (1) mixing an aqueous solution containing a copper salt with ammonia water to obtain a copper ammonia solution, mixing a carrier with the copper ammonia solution, reacting for I, and calcining for I to obtain the copper-loaded carrier;
[0008] (2) Mixing an aqueous solution containing a nickel salt with aqueous ammonia to obtain a nickel-ammonia solution, mixing the copper-loaded support obtained in (1) with the nickel-ammonia solution, performing reaction II, calcining II, and performing reduction treatment to obtain the copper-nickel-based catalyst.
[0009] (1), the copper salt is selected from at least one of copper nitrate, copper chloride, and copper acetate;
[0010] In the copper ammonia solution, the molar ratio of ammonia to copper salt is 100:1 to 2:1;
[0011] The molar amount of the copper salt is based on the molar amount of the copper element;
[0012] The carrier is selected from at least one of mesoporous silica, silica sol, white carbon black, activated silica, metakaolin, macroporous silica gel or molecular sieve;
[0013] The molecular sieve is at least one selected from X molecular sieve, MFI molecular sieve, Y molecular sieve, beta molecular sieve, and SSZ-39 molecular sieve.
[0014] The reaction I comprises the following process: stirring at 10-40° C. for 2-48 hours, and then raising the temperature to 70-100° C. until the pH of the solution is less than 8;
[0015] The temperature of the calcination I is 300-700° C.;
[0016] The calcination time is 1 to 48 hours.
[0017] (2), the nickel salt is selected from at least one of nickel nitrate, nickel chloride, nickel acetate, and nickel oxalate;
[0018] In the nickel-ammonia solution, the molar ratio of ammonia to nickel salt is 100:1 to 2:1;
[0019] The molar amount of the nickel salt is based on the molar amount of the nickel element;
[0020] The mass ratio of the copper-loaded carrier obtained in (1) to the nickel-ammonia solution is 1:0.3-500.
[0021] The reaction II comprises the following steps: standing at 25-30° C. for 2-24 hours;
[0022] Optionally, the reaction II comprises the following process: stirring at 10-40° C. for 2-48 h, then raising the temperature to 70-100° C. until the pH of the solution is less than 8;
[0023] The temperature of the calcination II is 300-700°C;
[0024] The calcination II takes 1 to 48 hours.
[0025] The atmosphere of the reduction treatment is a reducing gas atmosphere;
[0026] The reducing gas includes active gas and inactive gas;
[0027] The active gas is selected from at least one of hydrogen and methane;
[0028] The inert gas is selected from at least one of nitrogen, helium or argon;
[0029] The volume concentration of the active gas in the reducing gas is 5 to 100%;
[0030] The temperature of the reduction treatment is 200-600°C;
[0031] The temperature of the reduction treatment is 1 to 48 hours.
[0032] Specifically, the steps include:
[0033] Step 1: Preparation of copper-loaded silicon-based catalyst precursor:
[0034] (1) dissolving copper salt in water and stirring to obtain a copper salt solution;
[0035] (2) adding aqueous ammonia to the copper salt solution and stirring to obtain a copper ammonia solution, wherein the molar ratio of ammonia to copper salt in the solution is 100:1 to 2:1;
[0036] (3) adding the carrier to the copper ammonia solution, stirring at 10-40° C. for 2-48 hours, then raising the temperature to 70-100° C. to evaporate the ammonia solution until the pH of the solution is less than 8;
[0037] (4) filtering, washing, and drying the mixture, and then calcining at 300 to 700° C. for 1 to 48 hours to obtain the copper-loaded silicon-based catalyst precursor;
[0038] Step 2, preparation of copper-nickel based catalyst:
[0039] The copper-nickel based catalyst is prepared by introducing nickel into the copper-loaded silicon-based catalyst by an ammonia distillation method or an impregnation method;
[0040] The steps of preparing the copper-nickel based catalyst by ammonia distillation method are as follows:
[0041] (1) dissolving a nickel salt in water and stirring to obtain a nickel salt solution;
[0042] (2) adding aqueous ammonia to the nickel salt solution and stirring to obtain a nickel ammonia solution, wherein the molar ratio of ammonia to nickel salt in the solution is 100:1 to 2:1;
[0043] (3) adding the copper-loaded silicon-based catalyst precursor to the nickel-ammonia solution, stirring at 10-40° C. for 2-48 hours, then raising the temperature to 70-100° C. to evaporate the ammonia solution until the pH of the solution is less than 8;
[0044] (4) filtering, washing, and drying the mixture, then calcining it at 300 to 700° C. for 1 to 48 hours, and treating it with reducing gas at 200 to 600° C. for 1 to 48 hours to obtain the copper-nickel based catalyst;
[0045] The steps of preparing the copper-nickel based catalyst by the impregnation method are:
[0046] (1) dissolving a nickel salt in water and stirring to obtain a nickel salt solution;
[0047] (2) impregnating the nickel salt solution into the copper-loaded silicon-based catalyst precursor by an equal volume impregnation method or a partial impregnation method, and standing at room temperature for 2 to 24 hours after being fully mixed;
[0048] (3) drying the mixture, calcining it at 300-700° C. for 1-48 hours, and treating it with reducing gas at 200-600° C. for 1-48 hours to obtain the copper-nickel based catalyst.
[0049] According to another aspect of the present application, a copper-nickel based catalyst is provided, which is prepared by the above-mentioned preparation method.
[0050] The particle size of the metal particles supported in the copper-nickel based catalyst is 0.4 to 15 nm, and can be optionally 1.5 to 3 nm.
[0051] including a carrier and a metal active component;
[0052] The metal active components include copper and nickel;
[0053] The mass of the copper is 1 to 30 wt% of the mass of the copper-nickel based catalyst;
[0054] The mass of the nickel is 1 to 30 wt % of the mass of the copper-nickel based catalyst.
[0055] According to another aspect of the present application, a method for preparing acetonitrile by dehydrogenation of ethanol is provided, comprising at least the following steps:
[0056] Filling the catalyst into a reactor, introducing ammonia and ethanol to react, and obtaining acetonitrile;
[0057] The catalyst includes the copper-nickel based catalyst mentioned above;
[0058] The acetonitrile selectivity of the method is 80-99%; the ethanol conversion rate is 80-100%, and when the catalyst is stably operated for 200 hours, the bed pressure change is less than 0.1MPa.
[0059] The copper-nickel based catalyst is tableted and granulated, the tableting and granulation pressure is 1-10 MPa, and the particle size is 20-100 mesh;
[0060] The reactor is a fixed bed reactor;
[0061] The reaction temperature is 120-380°C;
[0062] Optionally, the reaction temperature is 220-350°C;
[0063] The reaction pressure is 0.1-1 MPa;
[0064] Optionally, the reaction pressure is 0.1-0.2 MPa;
[0065] The mass space velocity of the ethanol is 0.1 to 10 h -1 ; The ethanol is pumped in through a flow pump;
[0066] Optionally, the mass space velocity of ethanol is 0.1 to 5 h -1 ;
[0067] The molar ratio of ammonia to ethanol is 1 to 50;
[0068] Optionally, the molar ratio of ammonia to ethanol is 3-30.
[0069] This application has the following advantages:
[0070] 1. The present application provides a method for preparing a copper-nickel-based catalyst, and uses it for ethanol dehydrogenation amination reaction. The catalyst prepared by the method can significantly improve the yield of acetonitrile and reduce the generation of by-products during the reaction under low ammonia-alcohol ratio conditions. At the same time, the stability and service life of the catalyst are significantly improved. The catalyst provided by the present application has the advantages of simple operation, low catalyst cost, good stability, and high reaction efficiency.
[0071] 2. This application uses ethanol as a reactant to prepare acetonitrile. The ethanol output is large and the source is sufficient. The acetonitrile produced by the dehydrogenation amination reaction of ethanol has high added value and is widely used in many fields.
[0072] 3. The copper-nickel based catalyst prepared in this application has the following two advantages: 1) the sources of the carrier and the metal precursor are wide and inexpensive; 2) compared with single metal components, copper and nickel play a synergistic role in the catalytic reaction process, which can effectively reduce the activation energy of the reaction, and achieve high selectivity of acetonitrile under the harsh conditions of low reaction temperature and low ammonia-alcohol ratio, and the catalyst shows higher stability and reaction activity.
[0073] 4. The copper-nickel-based catalyst provided in this application is easy to prepare, low in cost, and has good stability. When used in the dehydrogenation and amination reaction of ethanol, the product is easy to separate and purify, and has good application prospects in the field of biomass conversion to produce high-value chemicals. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 This is a transmission electron micrograph of the sample obtained in Example 1 (the scale bar in the figure is 10 nm). DETAILED DESCRIPTION
[0075] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0076] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0077] Example 1
[0078] Preparation of copper-nickel based catalysts: Preparation of 15Ni / 15Cu-meso SiO2-AE catalyst by ammonia evaporation method
[0079] The process of preparing the catalyst is as follows:
[0080] Weigh 10.2g of copper nitrate and add it to a beaker containing 100mL of distilled water. Stir until completely dissolved, then slowly drop 24mL of 25% ammonia water. At this time, the pH of the solution is 12. Seal and stir vigorously for 90 minutes. Then add 19g of mesoporous silica powder to the beaker and continue to stir vigorously for 8h. Use a constant temperature water bath to raise the temperature to 90°C, and leave the beaker open to allow the ammonia in the system to evaporate until the slurry is neutral and stop stirring. After naturally cooling to room temperature, filter, wash the filter cake three times with deionized water, take out the filter cake and put it in a drying oven, dry it at 80°C for 8h, and then at 400. ℃ The catalyst was calcined at 400 °C for 2 h to obtain the copper-containing silicon-based catalyst precursor Cu-meso SiO2.
[0081] Weigh 11.7g of nickel nitrate and add it to a beaker containing 100mL of distilled water. Stir until completely dissolved, then slowly drop 26mL of 25% ammonia water. At this time, the pH of the solution is 12. Seal and stir vigorously for 90min. Then add 23g of Cu-mesoSiO2 powder to the beaker and continue to stir vigorously for 8h. Heat to 90°C in a constant temperature water bath, and leave the beaker open to allow the ammonia in the system to evaporate until the slurry is neutral, then stop stirring. After naturally cooling to room temperature, filter, wash the filter cake three times with deionized water, take out the filter cake and put it into a drying oven at 80 ℃ The catalyst was dried at 400℃ for 8h, calcined at 400℃ for 4h, and reduced at 300℃ for 3h in a hydrogen atmosphere to obtain a 15Cu / 15Ni-meso SiO2-AE catalyst prepared by ammonia evaporation method. The catalyst has a Cu content of 15wt% and a Ni content of 15%wt%. Figure 1 It can be seen that the particle size of metal Cu and Ni on the carrier in the catalyst is less than 3nm.
[0082] Example 2
[0083] Preparation of copper-nickel based catalysts: Preparation of 15Ni / 15Cu-meso SiO2-IM catalyst by impregnation method
[0084] The preparation steps of the copper-containing silicon-based catalyst precursor Cu-meso SiO2 are the same as those in Example 1.
[0085] Weigh 11.7 g of nickel nitrate, add it to a beaker containing 22 mL of distilled water, stir vigorously until completely dissolved, and then immerse an equal volume of nickel nitrate in 23 g of Cu-meso SiO2 powder. Let it stand at room temperature for 4 h, dry it at 80 °C for 8 h, and then calcine it at 400 °C for 4 h. ℃ After reduction for 1 hour, a 15Cu / 15Ni-meso SiO2-IM catalyst prepared by an impregnation method was obtained, wherein the Cu content of the catalyst was 15 wt%, and the Ni content was 15% wt%.
[0086] Embodiments 3 to 10
[0087] Example 3 is different from Example 1 only in that the copper-nickel based catalyst carrier is silica sol, and the catalyst number is 15Ni / 15Cu-sol SiO2-AE;
[0088] Example 4 is different from Example 1 only in that the copper-nickel-based catalyst carrier is a commercial molecular sieve silicate-1, and the catalyst number is 15Ni / 15Cu-silicate-1-AE;
[0089] Example 5 is different from Example 2 only in that the copper-nickel-based catalyst carrier is a commercial molecular sieve silicate-1, and the catalyst number is 15Ni / 15Cu-silicate-1-IM;
[0090] Example 6 is different from Example 1 only in that the copper content of the copper-nickel-based catalyst is 10wt%, the nickel content is 7wt%, and the catalyst number is 10Ni / 7Cu-meso SiO2-AE;
[0091] Example 7 is different from Example 1 only in that the copper content of the copper-nickel-based catalyst is 24wt%, the nickel content is 17wt%, and the catalyst number is 24Ni / 17Cu-meso SiO2-AE;
[0092] Example 8 is different from Example 2 only in that the copper content of the copper-nickel-based catalyst is 12wt%, the nickel content is 18wt%, and the catalyst number is 12Ni / 18Cu-meso SiO2-IM;
[0093] Example 9 is different from Example 2 only in that the copper-nickel-based catalyst carrier is white carbon black, the catalyst copper content is 12wt%, the nickel content is 18wt%, and the catalyst number is 12Ni / 18Cu-silica-IM;
[0094] Example 10 is different from Example 1 only in that the copper-nickel-based catalyst carrier is the commercial molecular sieve silicate-1, the catalyst copper content is 9wt%, the nickel content is 16wt%, and the catalyst number is 9Ni / 16Cu-silicate-1-AE.
[0095] Comparative Example 1
[0096] The only difference from Example 1 is that the step of loading Ni by ammonia evaporation is omitted, the copper content is controlled to 15wt%, and the obtained catalyst is 15Cu-meso SiO2-AE.
[0097] Comparative Example 2
[0098] The only difference from Example 1 is that the step of loading Cu by ammonia evaporation is omitted, the nickel content is controlled to 15wt%, and the obtained catalyst is 15Ni-meso SiO2-AE.
[0099] Comparative Example 3
[0100] The process of preparing the catalyst is as follows:
[0101] Weigh 10.2g of copper nitrate and 11.7g of nickel nitrate, add them to a beaker containing 100mL of distilled water, stir until completely dissolved, slowly add 31mL of 25% ammonia water, the pH of the solution is 12, seal and stir vigorously for 90min. Then add 19g of mesoporous silica powder to the beaker and continue to stir vigorously for 8h. Heat to 90℃ in a constant temperature water bath, and leave the beaker open to allow ammonia in the system to evaporate until the slurry is neutral and stop stirring. After cooling naturally to room temperature, filter, wash the filter cake three times with deionized water, take out the filter cake and put it in a drying oven, dry it at 80℃ for 8h, then calcine it at 400℃ for 2h, and reduce it at 300℃ for 1h in a mixed atmosphere of 10% hydrogen and argon to obtain a 15Ni / 15Cu-meso SiO2 one step-AE catalyst prepared by ammonia evaporation method with simultaneous loading of Cu and Ni.
[0102] Embodiment 11
[0103] The catalyst prepared in Examples 2 to 10 and Comparative Example 1 and Comparative Example 2 was used for ethanol dehydrogenation amination reaction. The catalytic conversion experiment was carried out in a fixed bed reactor under the following conditions: the amount of catalyst used was 5 g, the catalyst after tableting was added to the fixed bed reactor, and the temperature was raised to 260°C. Ammonia was introduced, and ethanol was pumped in at the same time, and the mass space velocity of ethanol was 1.0 h -1 , the molar ratio of ammonia to ethanol was 5, and the gas phase product was analyzed by online gas chromatography (Varian 3800, FID detector, capillary column PoraPLOTQ-HT). The reaction results of ethanol dehydrogenation amination catalyzed by different catalysts are shown in Table 1:
[0104] Table 1 Results of ethanol dehydrogenation amination reactions catalyzed by different catalysts
[0105]
[0106]
[0107] Table 1 compares the activity and product changes of ethanol dehydrogenation amination reaction on different catalysts. From the reaction data, it can be seen that the copper-nickel-based catalyst carrier, metal content and nickel loading method have a certain influence on the reaction results. The catalysts of Examples 1 to 10 all achieved an ethanol conversion rate of more than 80% and an acetonitrile selectivity of more than 80% in 200h. Compared with catalysts loaded with copper and nickel alone and catalysts loaded with copper and nickel in one step, the copper-nickel-based catalyst prepared by the two-step method has good reaction activity, high acetonitrile selectivity and good catalytic life.
[0108] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a copper-nickel based catalyst, It is characterized in that At least the following steps are included: (1) mixing an aqueous solution containing a copper salt with ammonia water to obtain a copper ammonia solution, mixing a carrier with the copper ammonia solution, reacting for I, and calcining for I to obtain the copper-loaded carrier; The reaction I The method comprises the following steps: stirring at 10 to 40° C. for 2 to 48 hours, and then raising the temperature to 70 to 100° C. until the pH value of the solution is less than 8; The temperature of the calcination I is 300-700° C.; The calcination time is 1 to 48 hours; The copper salt is selected from at least one of copper nitrate, copper chloride and copper acetate; In the copper ammonia solution, the molar ratio of ammonia to copper salt is 100:1 to 2:1; The molar amount of the copper salt is based on the molar amount of the copper element; The carrier is selected from at least one of mesoporous silica, silica sol, white carbon black, activated silica, metakaolin, macroporous silica gel or molecular sieve; The molecular sieve is at least one selected from X molecular sieve, MFI molecular sieve, Y molecular sieve, beta molecular sieve, and SSZ-39 molecular sieve; (2) mixing an aqueous solution containing a nickel salt with aqueous ammonia to obtain a nickel-ammonia solution, mixing the copper-loaded support obtained in (1) with the nickel-ammonia solution, performing reaction II, calcining II, and performing reduction treatment to obtain the copper-nickel-based catalyst; (2), the nickel salt is selected from at least one of nickel nitrate, nickel chloride, nickel acetate, and nickel oxalate; In the nickel-ammonia solution, the molar ratio of ammonia to nickel salt is 100:1 to 2:1; The molar amount of the nickel salt is based on the molar amount of the nickel element; The mass ratio of the copper-loaded carrier obtained in (1) to the nickel-ammonia solution is 1:0.3-500; The reaction II comprises the following steps: standing at 25-30° C. for 2-24 hours; The temperature of the calcination II is 300-700°C; The calcination II takes 1 to 48 hours.
2. The preparation method according to claim 1, It is characterized in that In (2), the reaction II comprises the following process: stirring at 10-40°C for 2-48 hours, and then raising the temperature to 70-100°C until the pH value of the solution is less than 8.
3. The preparation method according to claim 1, It is characterized in that (2), the atmosphere of the reduction treatment is a reducing gas atmosphere; The reducing gas includes active gas and inactive gas; The active gas is selected from at least one of hydrogen and methane; The inert gas is selected from at least one of nitrogen, helium or argon; The volume concentration of the active gas in the reducing gas is 5 to 100%; The temperature of the reduction treatment is 200-600°C; The temperature of the reduction treatment is 1 to 48 hours.
4. A copper-nickel based catalyst, It is characterized in that Prepared by the preparation method according to any one of claims 1 to 3; The particle size of the metal particles supported in the copper-nickel based catalyst is 0.4 to 15 nm, preferably 1.5 to 3 nm.
5. The copper-nickel based catalyst according to claim 4, It is characterized in that including a carrier and a metal active component; The metal active components include copper and nickel; The mass of the copper is 1 to 30 wt% of the mass of the copper-nickel based catalyst; The mass of the nickel is 1 to 30 wt % of the mass of the copper-nickel based catalyst.
6. A method for preparing acetonitrile by dehydrogenation of ethanol, It is characterized in that At least the following steps are included: Filling the catalyst into a reactor, introducing ammonia and ethanol to react, and obtaining acetonitrile; The catalyst comprises the copper-nickel based catalyst according to claim 4 or 5; The acetonitrile selectivity of the method is 80-99%; the ethanol conversion rate is 80-100%, and when the catalyst is stably operated for 200 hours, the bed pressure change is less than 0.1MPa.
7. The method according to claim 6, It is characterized in that The copper-nickel based catalyst is tableted and granulated, the tableting and granulation pressure is 1-10 MPa, and the particle size is 20-100 mesh; The reactor is a fixed bed reactor; The reaction temperature is 120-380°C; The reaction pressure is 0.1-1 MPa; The mass space velocity of the ethanol is 0.1 to 10 h -1 ; The ethanol is pumped in through a flow pump; The molar ratio of ammonia to ethanol is 1-50.
8. The method according to claim 6, It is characterized in that The reaction temperature is 220-350°C; The reaction pressure is 0.1-0.2 MPa; The mass space velocity of the ethanol is 0.1 to 5 h -1 ; The molar ratio of ammonia to ethanol is 3-30.
